To what extent are airlines communicating their commitment to sustainability issues? - Tornes, Maria (Høgskolen i Bodø, 2010)
Masteroppgave i bedriftsøkonomi - Høgskolen i Bodø, 2010 This thesis investigates Corporate Social Responsibility (CSR) in the aviation industry. The aim of the research is to analyse the extent to which these airlines are communicating their commitment to sustainability issues. The central question is essentially whether they are committed to the triple bottom line or to Milton Friedman's view that businesses need only follow the law? It is hard to measure commitment, but the first step in measuring commitment is to look at what these airlines are communicating to their stakeholders. This study uses a combination of content analysis and semi structured interview. The airlines in this study are Australian Virgin Blue and Qantas, British Silverjet, Asian AirAsia, and Scandinavian SAS. The elements of analysis are the annuaI reports, web pages, the Code of Conduct documents, an interview, and e-mail correspondence between the author and the airlines. This research uses the findings on these airlines to answer the central question and compares the findings to previous literature in the field of CSR. In conclusion this research shows that SAS and Qantas are communicating their commitment to sustainability issues to a greater extent in comparison to the other airlines in this study. SAS is in addition the only airline that follows through with its promises and is in addition showing its commitment through its open communication.